Particle resuspension in indoor environment - Yong, Cheng Hong. (2013)
The increasing concern of the effects of particle exposure on human health has increased the attention on particle deposition and resuspension in an indoor environment. High concentrations of particulate matter less than 2.5µm in size or PM2.5 is labelled as a health hazard. Bio-organisms such as bacteria, allergens, mites and spores fall within the size of 1-10µm. Resuspension of material By understanding the behaviour of particles in this size range, methods of mitigation can be devised. Two mathematical models are proposed estimate the airborne number concentration of the particles for deposition and resuspension. The deposition model allows the airborne number concentration at time, t to be estimated. The resuspension model allows an estimation of the airborne number concentration of the particles at time, t when a few parameters such as deposition velocity and resuspension rates are known. The behaviour of particles between 1-10µm in a turbulent indoor environment is also investigated in this project. The effect of the electrostatic force of attraction on particles is generally ignored in many experiments. However, it is observed to have a significant impact in the experiments on particles, especially those less than 5µm. After the anti-static spray is applied to the surface, decay constant for deposition with the fan on is observed to be reduced by up to 49.9%. The decay constant and deposition velocities are found to be higher when the fan is on as opposed to pure deposition.